Inovasi Mahasiswa Kampus Mengajar dalam Memfasilitasi Aktivitas Belajar Siswa - Ashilia Rizqi Hamidah; Minsih Minsih (Universitas Negeri Padang, 2024)
The campus teaching program represents a governmental initiative aimed at facilitating activities under the Merdeka Belajar-Kampus Merdeka (MBKM) scheme. It targets students across various academic disciplines in higher education, enabling them to play a part in enhancing elementary education, particularly in regions classified as 3T (Disadvantaged, Outermost, and Frontier). In the implementation of learning in schools, there are many educational problems. To overcome various educational problems as well as support various student learning activities, students of teaching campus 5 provide an innovation that is primarily to facilitate students in daily learning. The aim of this research is for the innovations created by students to hopefully address and solve various prevalent educational challenges. This research utilizes a qualitative methodology, adopting a case study strategy, and collects data through techniques including interviews, observations, and analysis of documents. This research provides results in the form of innovations made by teaching campus 5 students in providing innovative learning media and learning resources to facilitate student learning activities.